El registro más completo de un Hoplophorini (Xenarthra: Glyptodontidae) para los pisos/edades Chapadmalalense-Marplatense (Plioceno tardío-Pleistoceno temprano) - Zurita, Alfredo Eduardo (2011)
Glyptodontidae from southern South America are poorly known since most of the record are limited to remains of the dorsal and/or caudal armour. In this sense, the exceptions are represented by Paraglyptodon chapadmalensis (Ameghino in Rovereto), a fossil guide of the Upper Chapadmalalan Stage, and the Plohophorini Plohophorus figuratus Ameghino. On the other hand, the "Hoplophorinae" Hoplophorini are glyptodonts that have its first records during the Huayquerian (late Miocene) and "Araucanian" Stages (late Miocene-early Pliocene), but they are almost absents during the Chapadmalalan-Marplatan Stages (Pliocene-early Pleistocene). Later, the Hoplophorini (Neosclerocalyptus Paula Couto) are, together with Glyptodon Owen, the most common South American Pleistocene Glyptodontidae. In this contribution we report the first record of a Chapadmalalan Hoplophorini, assigned to the genus Eosclerocalyptus C. Ameghino (Eosclerocalyptus cf. E. lineatus), coming from the Mar del Plata locality, Buenos Aires province (Argentina). This new material, represented by a complete dorsal carapace, was exhumed from the upper section of the Chapadmalalan Formation. From a morphological perspective, this dorsal carapace shows an intermediate size between E. tapinocephalus Cabrera, E. proximus (Moreno & Mercerat) and Neosclerocalyptus Paula Couto. Together with cf. Paraglyptodon chapadmalensis and Plohophorus figuratus Ameghino those records represents the most entire Pliocene Glyptodontidae known and, in addition, it partially complete the stratigraphical distribution of the Glyptodontidae Hoplophorini.